A synchronous transition protocol with periodicity for global scheduling of multimode real-time systems on multiprocessors - Nélis, Vincent (2014)
We consider the global scheduling problem of multimode real-time systems upon identical multiprocessor platforms. During the execution of a multimode system, the system can change from one mode to another such that the current task set is replaced with a new task set. Thereby, ensuring that deadlines are met requires not only that a schedulability test is performed on tasks in each mode but also that (i) a protocol for transitioning from one mode to another is specified and (ii) a schedulability test for each transition is performed. In this paper, we extend the synchronous transition protocol SM-MSO in order to take into account mode-independent tasks [1], i.e., tasks of which the execution pattern must not be jeopardized by the mode changes.